UJI EFEK EKSTRAK ETANOL DAUN CINCAU HIJAU (Cyclea barbata Miers) SEBAGAI ANTIINFLAMASI PADA TIKUS PUTIH YANG DIINDUKSI KARAGEN - Irma Santi; Bayu Putra; Sri Wahyuni (As-Syifaa Jurnal Farmasi, 2017)
Inflammatory medication which is commonly used is the treatment synthetically or traditionally from the natural ingredients, the green grass jelly leaves (Cyclea barbata Miers). This research aimed to determine the effects and the most effective dose of the ethanol extract of green grass jelly leaves as an anti-inflammatory in white rats induced by carrageenan. This research used 15 mice divide into 5 group. Group I (negative control) was given Na.CMC; group II (positive control) was given Na.Diclofenac; group III, IV and V were given ethanol extract of green grass jelly leaves (EEDCH) at the dose of 1.875 mg/kgBW, 3.75 mg/kgBW, and 7.5 mg/kgBW. Pretreatment on animals induced by carrageenan 1% amounted to 0.1 mL in sub plantar on the soles of the mice. The measurements were made every 1 hour for 5 hour by using the pletismometer tool. The result showed that the ethanol extract of green grass jelly leaves has a potential as anti-inflammatory. Based on the result  of statistical analysis of the one way ANOVA followed by Post Hoc Test LSD showed that substance EEDCH at the dose of 7.5 mg/kgBW has anti-inflammatory effect were not significantly different from the positive control (Na.Diclofenac).Keywords: Green grass jelly leaves (Cyclea barbata Miers), anti-inflammatory, Na.Diclofenac.